Pengembangan Media Visual “PANJUMBAR” untuk Meningkatkan Kemampuan Operasi Hitung Penjumlahan pada Siswa Sekolah Dasar - Purwanti, Purwanti; Winarni, Retno; Prastiti, Tri Dyah (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2023)
The purpose of this research is to describe the process of developing Panjumbar learning media. Testing the effectiveness of the developed Panjumbar learning media. To find out the increase in natural number addition skills through the use of the developed Panjumbar learning media. This research is a type of Research and Development research or development research. Effectiveness analysis was carried out using the pretest-posttest results analysis. The pretest and posttest results were tested by Paired Sample T-Test. The results showed that the validity of panjumbar learning media by media expert validators for learning mathematics in class I of Gugus Sudirman Elementary School, Tirtomoyo District after revision, in terms of the educational aspect was 4.8 (very relevant), the technical aspect was 4.7 (relevant), aesthetics (very relevant). Thus the average validity of the media is 4.8 (very relevant). Material validity in terms of content aspect is 4.75 (relevant), construction aspect is 4.6 (relevant), language is 4.75 (relevant). Thus the average media validity is 4.8 (very relevant), and the average material validity is 4.75 (relevant). The effectiveness of Panjumbar media using the before-after experimental design in small group field trials is known to have an average pretest value of 73, and an average posttest value of 83.75. The average value of the large group pretest field test 71.13, posttest 81.56. This shows that the value of O2 is greater than O1, so the product design used in this study is effectively used as a medium for learning mathematics. Based on the normality test with the One Sample Kolmogorov Smirnov Test, the probability value of the t-statistic > Level of Significant = 0.05, namely the pretest value is 0.769 and the posttest value is 0.620 (> 0.05), thus the research data is normally distributed. The t test results obtained a significance value (2-tailed) 0.000 <0.05.